Consciousness, semiosis, and the unbinding problem. (May 2017) - Parthemore, Joel
Abstract: Any wider discussion of semiosis must address not only how semiosis came about, in terms of evolutionary pressures and requisite cognitive infrastructure, but also – as importantly, and too easily forgotten – how human beings experience and have experienced it, and how that experience reflects (at the same time shaping) its development. Much discussion has focused on resolving how inputs from external sensory modalities combine with internal brain processes to produce unified consciousness: the so-called binding problem . One might wish to distinguish between the coming together of conscious experience in terms of underlying mechanics and the seemingly unavoidable reality that human beings experience a consciousness that is, from the onset, phenomenally unified. The unbinding problem is shown to be potentially just as important to telling the story. Highlights: Understanding the origins of semiosis requires understanding the role of conscious experience. That conscious experience is phenomenally unified. Attempts to frame that phenomenal unity solely in terms of the binding problem fail. The proposed unbinding problem is just as critical to language's origins and evolution. "Just so"-like stories have an essential role to play in evolutionary accounts.